Does dividend policy mediate liquidity and profitability on firm value ? - Mariana Oktasia; Wendy Wendy; Anwar Azazi; Yulyanti Fahruna; Arman Jaya (Trigin Publisher, 2023)
This research aims to analyze the effect of liquidity and profitability on firm value mediated by dividend policy. This research employs the panel data regression analysis method by employing Eviews 12. This research analyzes 19 companies on the LQ45 index during 2018-2022, which were selected using a non-probability purposive sampling method. The data source in this research is secondary data obtained through the Indonesia Stock Exchange (IDX) website and several company websites selected as samples for this research. The findings of this research indicate that liquidity (CR) doesn't have any influence on dividend policy (DPR), profitability (ROE) has a negative effect on dividend policy (DPR), liquidity (CR) and profitability (ROE) have a positive impact on firm value (PBV). However, dividend policy (DPR) doesn't influence firm value (PBV). In addition, the findings of this research also indicate that dividend policy (DPR) can not be a mediator in the interaction between profitability (ROE) and liquidity (CR) with firm value (PBV).